Analysis of vectorcardiographic dynamic changes in patients with acute myocardial ischemia - Correa Prado, Raul Oscar (2013)
This work evaluates the vectorcardiographic dynamic changes in ischemic patients before and during Percutaneous Transluminal Coronary Angioplasty (PTCA). Four vectorcardiographic parameters were computed in 51 ischemic and 52 healthy subjects with the objective of assessing the differences between both groups: ST Vector Magnitude Area (STVMa), T Vector Magnitude Area (TVMa), ST Vector Difference (STVD), and T Vector Difference (TVD). The conventional ST-Change Vector Magnitude (STCVM) and Spatial Ventricular Gradient (SVG) were also calculated. Results indicate that the most of them show significant differences between healthy and ischemic subjects. Since, the statistical minute-by-minute PTCA comparison against a healthy population shows that ischemic patients monitoring reached values of Sensitivity = 99.5% and Specificity = 99.4%, when STVD, TVD and SVG were used in the classification. In conclusion the sensitivity and specificity for acute ischemia monitoring could be increase with the used of only three vectorcardiographic parameters.